Inclusive and adaptive business models for climate-smart value creation - Rosenstock, Todd S.; Lubberink, Rob; Gondwe, Sera; Manyise, Timothy; Dentoni, Domenico (Elsevier, 2020)
Climate-smart business models target multiple Sustainable Development Goals by fostering agricultural productivity, supporting farm and farmer livelihood resilience, and encouraging climate mitigation. While many business models (cl)aiming to create climate-smart value already exist both in agricultural development and business practice, little scholarly attention has so far been directed toward their functioning. In this paper, we argue that business models need to be inclusive and adaptive to generate climate-smart value equitably for all stakeholders involved and sustainably over time. Inclusivity involves not only providing the poor at the Bottom-of-the-Pyramid (BoP) with access to resources (e.g. finance, technology, access to markets) in business models but also, according to some scholars, with guaranteeing their representation in decision-making over the use of these resources. Adaptability entails the capacity to smoohtly adjust structures and processes of enterprise-BoP partnerships that underlie business models. We suggest that building inclusive and adaptive climate-smart business models is non-trivial work which, in the future, will require rapid cycles of collective experimentation and reflection between decision-makers in climate-smart business models and researchers studying them.